37th Joint Propulsion Conference and Exhibit 2001
DOI: 10.2514/6.2001-3868
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic instability in rockets

Abstract: Current solid-propellant rocket instability calculations (e.g., Standard Stability Prediction Program) account only for the evolution of acoustic energy with time. However, the acoustic component represents only part of the total unsteady system energy; additional kinetic energy resides in the shear waves that naturally accompany the acoustic oscillations. Because most solid-rocket motor combustion chamber con gurations support gas oscillations parallel to the propellant grain, an acoustic representation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…For example, in modelling the gas dynamics produced by solid propellant combustion, previous studies have ignored both viscosity and propellant regression by relying on Taylor's inviscid profile. Recent studies by Apte and Yang [32], Lee and Beddini [33,34], Flandro and Majdalani [35], and others have indicated the importance of retaining viscous corrections due to their appreciable contribution to the damping of vorticity waves. Thus, not only does viscosity alter the mean flow character, but it also affects the assessment of motor stability that is strongly influenced by vortical energy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in modelling the gas dynamics produced by solid propellant combustion, previous studies have ignored both viscosity and propellant regression by relying on Taylor's inviscid profile. Recent studies by Apte and Yang [32], Lee and Beddini [33,34], Flandro and Majdalani [35], and others have indicated the importance of retaining viscous corrections due to their appreciable contribution to the damping of vorticity waves. Thus, not only does viscosity alter the mean flow character, but it also affects the assessment of motor stability that is strongly influenced by vortical energy.…”
Section: Introductionmentioning
confidence: 99%
“…These instabilities occurring in the motor during the launch have been investigated (using analytical, experimental and numerical tools) by several researchers, both in the USA [5][6][7][8][9] and in Europe, 4,[10][11][12][13][14][15][16][17] within the frameworks of the ASSM (Aerodynamics of Segmented Solid Motors) and POP (Pressure Oscillation Program for the Ariane 5 solid booster, MPS P230) programs (an overview of these studies can be found in Fabignon et al 10 ) of CNES (Centre National d'Etudes Spatiales). Two-dimensional (axisymmetric and planar) numerical simulations were carried out to investigate the periodic vortex shedding and its effect on acoustic instabilities in a SRM.…”
Section: A Backgroundmentioning
confidence: 99%
“…It is characterized by oscillation in the gasification rate of the solid phase. 16 The transient response of premixed flames to acoustic waves has been numerically addressed by Chu et al 17 and Cai et al 18 after they developed a comprehensive theoretical/numerical model for treating AP/HTPB composite propellant combustion in a rocket motor environment. 19 In contrast, the interaction between thermo-acoustic oscillations and liquid fuel sprays has been the subject of many theoretical and experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there have been several studies into the interaction between the oscillations of the gas and the combustion zone in a SRM that have resulted in combustion oscillations, usually referred to as a “combustion response.” It is characterized by oscillation in the gasification rate of the solid phase. 16 The transient response of premixed flames to acoustic waves has been numerically addressed by Chu et al. 17 and Cai et al.…”
Section: Introductionmentioning
confidence: 99%